Evaluasi Penggunaan Teknik Arsir Linier dan Cross-Hatching Dalam Menggambarkan Volume Pada Sketsa Arsitektur - Sisca Novia Angrini; Randy Rizal; Reny Kartika Sary (Arsir: Jurnal Arsitektur, 2025)
In architectural education, the tools or media used to convey design ideas visually are usually sketch drawings. Architectural sketches have the aim of being an architect's initial representation and exploration to explain design concepts quickly and efficiently. In the depiction, there is a technique called shading technique. Generally, the most popular shading techniques are linear shading techniques and cross-hatching shading techniques. This research was conducted to explore the effectiveness of these two shading techniques in the architectural education curriculum in Indonesia. The method used is a qualitative approach with the respondents being students of the Architecture study program at the Universitas Muhammadiyah Palembang. Data processing uses thematic analysis techniques that identify the strengths and weaknesses of each shading technique. The categorized aspects consist of volume, depth and lighting. After processing the data, it was found that the cross-hatching shading technique was more effective in producing voluminous images with depth and realistic lighting effects. Although on the other hand, students find it difficult and spend a lot of time completing the cross-hatching shading technique. Research findings show that the selection of shading techniques in architectural education still needs to be done in stages. Curriculum development needs to systematically integrate learning of all shading techniques.